Evaluation of Stroke Risk in Patients With Atrial Fibrillation Using Morphological and Hemodynamic Characteristics - Wang, Lingfeng; Wang, Zidun; Fang, Runxin; Li, Zhi-Yong (Frontiers in Cardiovascular Medicine, 2022)
Background It is well known that the thrombus triggering stroke in patients with atrial fibrillation (AF) mainly comes from the left atrial appendage (LAA). This study aims to characterize the morphological and hemodynamic parameters and evaluate their differences between AF patients with and without a stroke history. Methods Cardiac CT images were obtained from AF patients with (n = 10) and without a history of stroke (n = 10). 3D models of the left atrium (LA) were reconstructed by processing the CT image, and the LA/LAA morphological parameters were measured. Computational fluid dynamics (CFD) simulations were performed to calculate the hemodynamic parameters in LA. The species-transport model and discrete phase model (DPM) were applied to analyze blood residual ratio and particle residual ratio, two qualitative parameters for thrombus formation and flow-out potential, respectively. Results There were significant differences in LAA actual depth (p = 0.002), and direct length (p = 0.049) between the non-stroke and stroke groups. Significant differences were also found in certain hemodynamic parameters. The blood residual ratio in LAA was significantly smaller in the stroke group than in the non-stroke group (p < 0.05). Moreover, the particle residual ratio within LAA was significantly smaller in the stroke groups than in the non-stroke group (p < 0.05). Conclusion There are significant differences in both morphological and hemodynamic parameters between AF patients with and without a stroke history. A high blood residual ratio in LAA confirms that thrombus is more likely to form in AF patients. A significantly smaller particle residual ratio in the stroke group may suggest the thrombus formed with LAA is more likely to flow out of LAA, leading to a higher risk of stroke. The proposed morphological and hemodynamic parameters may be additional risk factors that can be used to better risk stratify AF patients.